Tile vaults as integrated formwork for reinforced concrete: Construction, experimental testing and a method for the design and analysis of two-dimensional structures. (1st June 2019) - López López, David; Roca, Pere; Liew, Andrew; Van Mele, Tom; Block, Philippe
Highlights: Proposal of efficient construction method for RC shells using tile-vaulted formwork. Presentation of design and structural analysis method for such 2D composite structures. Validation of limit-analysis method through experimental research. Application of method to shape and material optimisation. Abstract: Tile vaults are traditional, unreinforced masonry structures made of thin bricks (tiles), mortar and fast-setting cement or gypsum. They can be constructed without the need for a formwork, except at the boundaries, making them inherently economic. Tile vaults have historically provided a solution for the efficient construction of vaulted structures. Today, they can be used as permanent formwork for concrete shells, allowing for a significant reduction of the construction cost and waste produced, due to the possibility of reducing or even eliminating the need for traditional formwork. The concrete can be poured directly onto a tile-vaulted formwork to form a composite structure. This paper presents a technique for the construction of single-curvature shells consisting of a composite structure combining tile vaulting and reinforced concrete. A method for the design of these composite vaults and the assessment of their strength and stability against external loading is also presented. This method is based on limit analysis but takes into account the reinforcement's contribution to the composite cross-section's bending capacity. The equilibrium method is implemented computationally to provide fast results for the user. It provides graphical and intuitive results and opens the possibility for the future extension to fully three-dimensional problems. The design and structural analysis method is called Extended Limit Analysis for Reinforced Masonry (ELARM). Both the proposed construction technique and the computational method have been validated through experimental research. The feasibility of the building technique has been validated by the construction of two full-scale prototypes. In addition, the prototypes have been load-tested to failure to compare the results with those predicted by ELARM.